Approach and Treatment of Giant Luminal Unicystic Ameloblastoma - George Borja de Freitas; Evelyne Pedroza de Andrade; Riedel Frota Sá Nogueira Neves; Stefanny Torres dos Santos; Daniella Cristina da Costa Araújo; Victor Ângelo Montalli (Hindawi Limited, 2018)
Unicystic ameloblastoma is an odontogenic tumor that affects mainly young patients and usually involves the posterior region of the mandible. In this article, we report on the case a 12-year-old girl presenting with an 8-month history of facial swelling in her lower right quadrant. Radiographic examination revealed a unilocular radiolucent lesion extending from the body of the mandible through to the angle and ascending ramus. An incisional biopsy was performed, and a diagnosis of luminal unicystic ameloblastoma was made based on clinicopathological features. The lesion was treated in two stages, namely, an initial conservative approach via decompression and subsequent excision. The patient has been followed up for 6 months without clinical and radiographic evidence of recurrence. In conclusion, conservative timely intervention combined with a conservative surgical approach has proven efficacious in the treatment of ameloblastoma in this young patient.